2010
DOI: 10.1007/s12665-010-0585-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between electrical capacitance-based dielectric constant and soil water content

Abstract: Based on batch experiments conducted on soil samples in the laboratory, the relationship between dielectric constant and water content based on electrical capacitance measurement was investigated. Factors that may affect the relationship, such as measurement frequency, electrode array methods, and soil particle sizes, were analyzed. A model fitting the relationship between dielectric constant and water content was proposed. The results clearly indicate that even with the use of rod-like sensors, the measured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The next equation comes from [25], which is using coaxial transmission system and using soil samples with wide range of soil textures: θ ¼À0:0286 þ 0:02435ε À 0:0003421ε 2 þ 0:00000237ε 3 (13) Equations (5)- (8) are used for measurement at a frequency of 100 MHz. [13] proposed an empirical model where permittivity measurement was measured based on capacitance. This experiment used a type of quartz sand with a range of particle sizes between 0.15 and 0.9 mm:…”
Section: Model With One Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…The next equation comes from [25], which is using coaxial transmission system and using soil samples with wide range of soil textures: θ ¼À0:0286 þ 0:02435ε À 0:0003421ε 2 þ 0:00000237ε 3 (13) Equations (5)- (8) are used for measurement at a frequency of 100 MHz. [13] proposed an empirical model where permittivity measurement was measured based on capacitance. This experiment used a type of quartz sand with a range of particle sizes between 0.15 and 0.9 mm:…”
Section: Model With One Parametermentioning
confidence: 99%
“…Various techniques in the measurement of contamination and water content of soil have been discussed in literatures (e.g., [7][8][9][10][11][12]). Based on previous studies, soil water content measurement techniques are widely used as an electromagnetic method [13] such as time domain reflectometry [14], ground-penetrating radar (GPR) [8], and electrical capacitance [15]. These all methods measure the value of relative permittivity of soil to find soil moisture water content.…”
Section: Introductionmentioning
confidence: 99%
“…Dielectric detection technology is based on the interaction of external electric field to the internal physiological and chemical changes of the sample (Hamed, Zorrig, & Hamzaoui, ; Wu, Zhou, Wang, Yang, & Ling, ; Zhang, Zhou, Ling, & Wang, ). It could represent the whole sample information, and mainly described by the relative dielectric constant, dielectric loss factor, and dielectric loss angle tangent (Davis, Matovic, & Pollard, ; Pan, McDonald, Via, Fulton, & Hung, ).…”
Section: Introductionmentioning
confidence: 99%
“…Through comparative analysis of various methods and theories, we concluded that the dielectric method was the most promising one. Among the dielectric methods, capacitance method has unique advantages compared with other dielectric methods, including (1) the ability to measure dynamic conditions [13]; (2) low cost of the measurement instruments and minimal site disturbance [14]; and (3) the adaptivity of the sensor geometry, facilitating the development of a variety of configurations [15]. It can be seen that the capacitance method may have great potential in dynamically capturing soil/soilless substrate water content practically.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, based on equation (11)-(13), we can derive the sensor in air and water are U 0 and U 1 respectively; equation(14) results in…”
mentioning
confidence: 99%